CONDITION, PROBLEMS AND TRENDS OF MEDICO-SOCIOLOGICAL RESEARCHES OF PUBLIC HEALTH AND HEALTH SYSTEM - Андрей Александрович Кожевников (Медицина в Кузбассе)
In article by the analysis of domestic and foreign publications, other information sources the most popular are considered and the methodological approaches having practical application connected with assessment of public health and a health care system. A predictive conclusion about what unlike other types of ensuring medical activity of medico-sociological providing allows to expand idea of activity of subjects of a health care system due to establishment of target interrelation of socially oriented integrated indicators is formulated, to estimate health and quality of life of the population.